A study on transport services : Options on eligible users of transport when move to KLIA Sepang in 1998 / Hanita Sufia Hamzah - Hanita Sufia, Hamzah (Faculty of Architecture, Planning and Surveying, 1997)
Transport means movement of people or goods from one point to another, or where the value might be greater. Transportation is a derived demand which bridges the gap between two points. Whatever activities to be performed will involve transportation. In economic world, transport acts as a back bone whereby without it the economic activities will be paralysed. As in an airline company .other than the aircraft operation, transportation is crucial to bring the crew to and from the airport punctually to avoid any delay in aircraft departure. This study will focus on the transport provision for both cabin crew and technical crew, and also the role of Transport Department. MAS will be moving its flying operation to KLIA Sepang by 1st January 1998. Therefore, transport provision for the crew will be affected because the base and the coverage have changed. Even the existence of the MAS Transport Department is in uncertainty. This study is conducted as a means to evaluate the importance of providing transport service for the crew. Besides that, it will also look at some proposed options regarding transport operations when move to KLIA Sepang which is prepared by Transport Services Department. Analysis is done to find out which option is the best to be adopted.